A Study Coastal Protection Using Stones Crushed and Tetrapod (Case study at Ujong Blang Beach) - Teuku Muhammad Ridwan; Abdul Jalil (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Ujong Blang Beach and Jagu Beach are in Lhokseumawe City. The purpose of this study was to plan a breakwater along the coast of Ujong Blang as an alternative for coastal protection. This includes specifying the details of the breakwater layers and calculating the dimensions of the breakwater. Applying the Hudson method to obtain the diameter and weight of stones grains. The protective layer material uses crushed stones and tetrapods. The results of the analysis obtained breakwater dimensions obtained based on a slope of 1: 2. The results of the analysis that have been obtained are made in the drawing 2D as a result of designing rock mounds with a slope of 1: 2. Breakwaters are planned in a position to protect the coast from waves. The planned breakwater height is 6.32 meters so it has the same elevation and crest dimensions, but the material volume will change less due to the lower contour differences in the sea.This type of breakwater is suitable for Ujong Blang beach, because it will have a good effect on the tourism business. The number of protected layer grains on a slope of 1:2 has a material use of 0.23 tons of tetrapods and a peak width of 3.5 meters.